Illustrating a sentimental journey: Kate O'Brien's Farewell Spain. Issue 2 (3rd April 2017) - Davison, Jane
ABSTRACT: When the Spanish Civil War broke out in 1936 the Irish novelist and playwright Kate O'Brien felt compelled to respond. The result was her travelogue, Farewell Spain (1937 ). O'Brien's antipathy for the Franco regime is apparent as she takes the reader on a sentimental journey that is accompanied by a series of 13 pencil-drawn illustrations by Mary O'Neill. A series of letters between O'Brien and Charles Evans, her publishing editor at William Heinemann Ltd, reveals a compelling debate over the aesthetic importance of O'Neill's illustrations and O'Brien's staunch refusal to permit her travelogue to be published without them. This article argues for a re-evaluation of the significance of the illustrations to Farewell Spain by exploring their role in illuminating O'Brien's aesthetic and the extent to which the personal relationship between author and illustrator was a motive for their inclusion.